ANALISIS FAKTOR - FAKTOR YANG BERPENGARUH TERHADAP AUDIT DELAY (Studi Empiris Pada Perusahaan - Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2012 - 2014) - Erni Riana Wulansari, 12.05.52.0082; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2016)
This study is a study that examined the effect of corporate financial reporting to the audit delay. Audit delay is the open interval of number of days from the year end to the date recorded as the opinion signature date in the auditorâs report.Â In this study, the sampels used by 693 companies that listed on the Indonesian Stock Exchange in the year 2012 to 2014. Sampels choosed by purposive sampling method. In this study, the dependent variabel is audit delay. And the independent variables are profitability, solvability, firm size, auditorâs opinion, public accountan size, auditorâs gender, profit and loss of the firm, and audit committee.Â The results indicate that firm size, auditorâs opinion, profit & loss, and audit committe showed negative effect on audit delay. Auditorâs gender showed positive effect on audit delay.Profitability, solvabilty, and public accountant size have no effect on audit delay.Keywords: Audit Delay, Profitability, Solvability, Company Size, Auditorâs Opinion, Public Accountant Size, Auditorâs Gender, Profit And Loss Of The Company, Audit Committee